Decision-making in ethical dilemmas faced by auditors: a case study of small and medium sized audit firms that are trusted by the stock exchange - Maryam Rokhshi; Kaveh Azinfar; Seyyed Ali Nabavi Chashmi (تصمیم گیری و تحقیق در عملیات)
Purpose: The purpose of this research is to examine auditors' decision making in the face of ethical dilemmas in small and medium sized audit firms that are trusted by the stock exchange. This research seeks to investigate the relationship between the effective factors (such as auditor experience, audit firm size) on auditors' ethical decisions and to evaluate the role of these factors on audit quality and accuracy.Methodology: The statistical population in this study consists of the trusted auditing firms of the stock exchange, which includes 77 firms that have been studied by the full number method. The data of this research have been collected through the design of questionnaires among the auditors of small and medium audit firms trusted by the stock exchange. The collected data were analysed using SPSS20 statistical software and qualitative analysis techniques.Findings: Four hypotheses were stated for this research. The results of the research show that audit experience and ethical decision making on audit problems (dilemmas) have a meaningful relationship. The results show that the size of the audit firm and ethical decision-making in audit problems (dilemmas) do not have a significant relationship. Also, there is no significant relationship between the ethical decision-making of audit problems (dilemmas) and the pressure received by the auditor from the client (employer) or the auditing firm.Originality/Value: This research can help improve the quality of audits in small and medium enterprises and increase public confidence in financial reports. Also, the results of this research can help policy makers and regulators to establish more effective rules and regulations to support the independence and professional ethics of auditors through a better understanding of the ethical challenges faced by auditors.